Increasing Competence in Compiling Teaching Materials through Assistance in the Development of Teaching Materials for Lecturers - Pradana, Hirnanda Dimas; Mustaji, Mustaji; Arianto, Fajar; Kristanto, Andi (International Journal of Community Service Learning, 2023)
Teaching materials are an integral part of learning. Teaching materials will always develop according to technological and scientific developments. IAI Al-Khairat lecturers need an activity to help them improve their ability to compile the latest teaching materials. This mentoring activity for preparing teaching materials aims to assist lecturers in producing teaching materials that are by the characteristics of courses and students in the IAI Al-Khairat Pamekasan Madura environment. The development of teaching materials is one of the performance indicators used to evaluate the contribution of lecturers to the university's main performance indicators. Teaching materials in the main performance indicators can be used to show that the community uses them. Assistance in the development of teaching materials is carried out using the project-based learning method, where participants will produce drafts of course teaching materials. The subjects of this training activity were IAI Al-Khairat Pamekasan lecturers, totalling 30 lecturers. As a result of the training activities, lecturers can compile teaching materials on the subjects that are well taught and by the times. This activity concludes that the competence of lecturers in developing teaching materials is increasing.